2018
DOI: 10.1002/hpja.46
|View full text |Cite
|
Sign up to set email alerts
|

Developing a culturally appropriate branding for a social and emotional wellbeing intervention in an Aboriginal community

Abstract: The approach of using a logo competition to develop the campaign brand was highly successful and enabled further meaningful engagement with the community and other service providers in the town. The success of the competition process resulted from an emphasis on relationship building, listening to the local community and involving the community in decision-making. So what? By conforming to established, but not always adhered to, recommendations for community consultation, successful and more enduring outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…This intensification is illustrated in the training of volunteers and frontline personnel in both Denmark and Australia, and also in the specific sub-programs in Australia that have focussed on training mental health professionals to help people in recovery to 'act-belong-commit', and the very focussed community approach in a remote Aboriginal community in the North of Western Australia (Wedin et al, 2016;Donovan et al, 2018). The last, in particular, called 'Standing Strong Together in Roebourne', is very focussed on building on existing community strengths, bringing groups together to work on common town issues and fostering community cohesion, resistance resources and shared goals to improve the local physical, social and political environment.…”
Section: Wwwmentallyhealthywaorgaumentioning
confidence: 99%
“…This intensification is illustrated in the training of volunteers and frontline personnel in both Denmark and Australia, and also in the specific sub-programs in Australia that have focussed on training mental health professionals to help people in recovery to 'act-belong-commit', and the very focussed community approach in a remote Aboriginal community in the North of Western Australia (Wedin et al, 2016;Donovan et al, 2018). The last, in particular, called 'Standing Strong Together in Roebourne', is very focussed on building on existing community strengths, bringing groups together to work on common town issues and fostering community cohesion, resistance resources and shared goals to improve the local physical, social and political environment.…”
Section: Wwwmentallyhealthywaorgaumentioning
confidence: 99%
“…The adaptability of the Act-Belong-Commit domains across cultures illustrates the universality of these three domains as shown in the following examples: a pilot program in a First Nations community in Western Australia showed that the message was consistent with Indigenous people’s concepts around social and emotional wellbeing and was readily modified for a local implementation [ 48 ]; the campaign was adapted in Japan for children after the 2011 tsunami [ 49 ]; and the campaign has attracted partner organisations in the UK and USA and is being implemented in Denmark, the Faroe Islands and Norway [ 23 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…As stated in Reason #11, the Act-Belong-Commit messages can be promoted in media channels to reach and impact the whole population. However, to intensify that impact, the Act-Belong-Commit messages can be readily tailored to specific socio-demographics or sub-populations such as: children and adolescents; new mums and dads; individuals along the spectrum from flourishing to unwell; individuals in recovery from a mental illness or drug addiction; people with a disability; retirees and the elderly; migrants and various ethnic groups [ 3 , 48 , 49 , 67 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it was decided to engage with an Aboriginal community in Western Australia to determine whether the basic Act-Belong-Commit constructs were accepted as consistent with Aboriginal people's views on social and emotional well-being, and, if so, how the campaign could be culturally adapted and implemented in the community. As anticipated and outlined in Donovan et al (2018a), consultation with the community revealed acceptance of the campaign principles and a subsequent relatively straightforward cultural adaptation of the campaign.…”
Section: Act-belong-commit Mental Health Promotion Campaignmentioning
confidence: 75%